Quality of Life for Patients with Heart Disease: Limitations and Remedial Actions - Chakrabartty, Satyendra Nath (Indian Journal of Pharmacy Practice)
Background: Various generic and disease-specific scales used for assessment of Health-Related-Quality of Life (HRQOL) in patients with Coronary Heart Disease (CHD) consider items which differ in formats, chosen domains, scoring systems. Discrete scores generated by such scales fail to satisfy equidistant property for addition. Analyses do not consider distributions of item scores or scale scores. Materials and Methods: The methodological paper provides an assumption-free method to convert discrete, ordinal item scores to continuous equidistant scores following normal distribution in the score-range 1 to 100 to ensure non-negative scores. Sum of normally distributed transformed item scores are taken to find Domain scores and scale scores, each following normal. Results: The proposed scores result in meaningful arithmetic aggregation and avoid major limitations of getting test scores as sum of raw item scores and facilitate parametric analysis, meaningful comparisons, ranking and classification, responsiveness of the scale i.e. assessment of changes across time at individual level or for a sample of individuals and helps to draw progress-paths. Normality also helps to estimate population parameters, finding equivalent scores of scales and psychometric features like factorial validity, discriminating value and reliability. Conclusion: Normally distributed scores improve scoring of instruments relating to health outcomes of surviving-patients with CHD. Health care professionals and researchers can take advantages of the proposed method satisfying desired properties, including detection of changes by longitudinal data and evaluating psychometric parameters at population level.
Keywords: Cardiovascular diseases; Quality of Life; Normal distribution; Transformation; Assessment of progress; Population estimates